Comparative Study of Nutrients and Anti-Nutrients Composition of Commonly Consumed Edible Grasshopper (Chorthippus brunneus), Locust Beans (Parkia Biglobosa) and Soya Beans (Glycine max) in Katsina State - Abubakar, M.; Abdullahi, N. (UMYU Journal of Microbiology Research)
The purpose of this study is to evaluate the nutrients, anti-nutrients and minerals composition of edible grasshopper (Chorthippus brunneus), locus beans and soya beans. The evaluations of nutrients and anti-nutrient composition of Chorthippus brunneus, Parkia biglobosa and Glycine max were analyzed using standard methods of A.O.A.C. and Kjedahal methods. The proximate analysis revealed that crude protein ranged between 24.667±3.512 to 39.561±2.553 with Chorthippus brunneus having the highest value and Parkia biglobosa and Glycine max having the lowest values. The Chorthippus brunneus had a considerable low carbohydrate contents compared to P. biglobosa and G. max carbohydrate value. However, the mean energy/caloric values ranged from 474 to 522 Kcal/Kg. Crude fat values were moderate, ranging from 11.763±1.035 to 15.26±0.761 with G. max having the highest value and C. brunneus the lowest. The anti-nutrients of the insects and the legumes were generally below toxic level in man. Moisture, ash and crude fibre were very high in C. brunneus compared to Parkia biglobosa and Glycine max. These Chorthippus brunneus therefore, could serve as additional promising sources of protein and fat for poultry and teeming population. The mineral compositions of the inscts (mg/kg) were considerably lower than that of locus beans and soya beans.